Efektivitas Promosi Gizi Seimbang dan Aktivitas Fisik terhadap Pengetahuan dan Perilaku Sehat Remaja - Jein Jeilen Tampi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2025)
Adolescent health serves as a critical foundation for shaping a productive and high-quality future generation. However, low awareness of healthy eating and lack of physical activity remain major challenges among teenagers today. This study aims to evaluate the effectiveness of promoting balanced nutrition and physical activity in improving students’ knowledge and healthy behavior. A quantitative method was applied using a quasi-experimental one group pretest-posttest design. The sample included all 205 twelfth-grade students of SMA Negeri 7 Manado. The intervention consisted of health education sessions, interactive discussions, and the use of educational visual media within the school environment. Wilcoxon test results showed a significant increase in knowledge and behavior scores after the intervention (p = 0.000). These findings confirm that a systematically designed and interactive school-based health promotion program is effective in enhancing awareness and establishing healthy lifestyle habits among adolescents..